The Effect of Gamma Radiation Induced Sterility in Potato Tuber Moth Phthoriamaea operculellea Zeller (Lepidoptera: Gelechiidae) - Naji, M. A.; Kafu, A. A.; Mahfoud, N. A.; Maghrabi, H. A. (The Libyan Journal of Science, 2018)
A total of 400 pupae/cage were transferred into sterilized cages for laboratory rearing of potato tuber moth, PTM, Phthorimaea operculella Zeller at the Agriculture Research Center, Tripoli. Emerged adults in each cage fed 10% sugar solution on soaked wicks. After mating and ovipostion eggs were collected daily. A batch of cleaned and sterilized potatoes was punctured and tubers infested with PTM white eggs. After hatching larvae find their way into tuber through entrance holes. Infested potatoes were placed in rearing trays to pupate in the sand. Pupae were collected, sieved and removed into sterile rearing cages for adults emergence. Adult male parents 24h old were radiated with gamma radiation 100, 150 and 200 Gy at the Nuclear Research Center, Tajura. Adult mating crosses including control were evaluated for the effects of induced gamma radiation sterility in PTM. Significant differences of gamma radiation effects to PTM male parents were observed for reduction counts of eggs, pupae and adult males at 0.05 level and females at 0.001 level for 150 and 200 Gy gamma radiation doses. This study indicates that the use of sub-sterilizing doses of gamma radiation could be considered as an important component in the IPM control strategy.